ISOLATION AND CHARACTERIZATION GLUCOMANNAN FROM DIFFERENT TYPES OF TALAS (Colocasia) AND ILES-ILES (Amorphophalus oncophyllus) - Diova Ritonga, Anggrena
Talas and iles-iles have great benefits to be processed into food and carbohydrate substitution. In some areas of Indonesia, talas and iles-iles used for additional food or subtitute food, especially in lean times. One component of carbohydrates in talas is glucomannan. Glucomannan is a polysaccharide of the mannan family, which is very abundant in nature, especially in soft wood (hemicellulose), roots, tubers and woody plants. Glucomannan is a polysaccharide with a ?-1,4 linked composed by two units of monomers, that is, D-glucose and D-mannose, in the ratio of 1:1,6. Besides from being a source of food, glucomannan can be used as edible film, capsule ingredient, celluloid tape, and the metal ion adsorbents. The purpose of this research was to determine content and characterization of glucomannan from diverse species of talas (Colocasia) (by using two species: talas lubang, and talas hitam), iles-iles (Amorphophalus oncophyllus), high and low viscosity glucomannan flour. The glucomannan was extracted by water solvent, and then precipitated by using a 95% ethanol in the ratio of water to ethanol 1:4,5 v/v. The precipitate formed was washed twice with anhydrous ethanol (dehydration process), and then isolated by vacuum filtration, before being freeze-dried for 48 hours. The dried material is milled and sieved, thus resulting are glucomannan purification results. Characterization of glucomannan performed using an infrared spectrophotometer, 1H-NMR, 13C-NMR, and the content calculated using a spectrophotometer UV/VIS with sulfuric acid - phenol method. The results of 1H-NMR spectra and 13C-NMR showed the existence of proton and carbon anomer from samples that have been isolated. The chemical shifts for proton anomer in the 1H-NMR spectrum (mannose/glucose) for talas hitam is 5,170/4.70 ppm, iles-iles 4.68/4.37 ppm, low viscosity glucomannan flour 4.612/4.373 ppm, and high flour viscosity glucomannan 4.683/4.380 ppm. In the 13CNMR spectrum, the chemical shift for carbon anomer (mannose / glucose) of iles-iles is 100.13/102.89; 102.85 ppm, and low viscosity glucomannan flour was 100.1/102.80 ppm. Infrared spectra showed the existence of absorption at wavenumbers for talas hitam, iles-iles, low viscosity glucomannan flour, and high viscosity glucomannan flour of 812.39 cm-1, 808.17 cm-1, 810.10 cm-1, 810.10 cm-1, respectively, indicating the existence of a ?-1,4 linked from D-glucose and Dmannose. The small peak at wavenumber ~1700 cm-1 is due to C=O stretching vibration. Intensity of carbonyl peak for talas hitam higher than the other samples, this is because talas hitam has more acetyl groups. Glucomannan has an acetyl group in 10-19 units each carbon group at position C2, C3 and C6. Based on the data of infrared and NMR spectra of each sample, the isolated compounds are glucomannan.The contents of glucomannan as the result of the isolation from talas hitam, talas lubang, iles-iles, low viscosity glucomannan flour, and high viscosity glucomannan flour were 0.39%, 0.52%, 14.38%, 25.93% , and 21.41%, respectively. From the research, the highest content of glucomannan is the low viscosity glucomannan flour, in the amount of 25.93%. High or low content of glukomannan in iles-iles plants is influenced by many factors including: type of plant, pre-treatment before drying, harvest, milled parts, tool use, tool rotation speed grinder, grinding repetition time, age of the plant, and how to process it.